2019
DOI: 10.1186/s12913-019-3918-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gaps in care for malnourished patients on length of stay and hospital readmission

Abstract: BackgroundFew published articles have focused on identifying the gaps in care that follow a malnutrition diagnosis and their effects on length of stay (LOS) and 90-day readmission. We hypothesized that length of stay and readmission were associated with these gaps in care.MethodsTwo registered dietitians retrospectively reviewed charts of 229 adult malnourished patients admitted to a medicine unit to determine their system level gap in care: communication, test delay, or discharge planning. In this secondary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Admissions with malnutrition diagnoses required a longer LOS, consistent with existing literature 26–29 . We also found that malnutrition inpatient encounters were more likely to be admitted through the emergency department and were associated with an increase in opioid prescription.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Admissions with malnutrition diagnoses required a longer LOS, consistent with existing literature 26–29 . We also found that malnutrition inpatient encounters were more likely to be admitted through the emergency department and were associated with an increase in opioid prescription.…”
Section: Discussionsupporting
confidence: 87%
“…24,25 Admissions with malnutrition diagnoses required a longer LOS, consistent with existing literature. [26][27][28][29] We also found that malnutrition inpatient encounters were more likely to be admitted through the emergency department and were associated with an increase in opioid prescription. Early identification and treatment of at-risk patients for could lead decreased LOS and emergency department visits.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…1.3,1.3, and 2.6 times, respectively, more likely to have a shorter LOS than patients who were underweight, had lower MUAC, and lower dietary diversity(Abrha et al, 2019).Regardless of the nutritional complications and implications that come hand in hand with malnutrition, there are several other reasons why malnutrition impacts length of stay Ringel et al (2019). suggested the presence of three gaps in the system that could translate into longer length of stay for malnourished patients: communication, delay in testing, or discharge planning.…”
mentioning
confidence: 99%